GC/MS profile and antifungal activity of Zanthoxylum caribaeum lam essential oil against Moniliophthora roreri cif and par, a pathogen that infects Theobroma cacao l crops in the tropics (2023)
The species Zanthoxylum caribaeum belongs to the Rutaceae family, from which several chemical nuclei are known, including alkaloids and coumarins. In addition, its essential oil has been characterized, showing differences in composition and various antimicrobial activities. In the present study, the essential oil of Z. caribaeum collected in the department of Tolima, central Colombia, was characterized by gas chromatography with mass selective detector (GC-MS). The essential oil showed a composition of about 43 compounds (including major and minor), whose main components, according to their abundance, are the following: germacrene D (228.0 1.6 mg/g EO), (E)–farnesene (128.0 1.5 mg/g EO), -elemene (116.0 1.6 mg/g EO) and (E)-nerolidol (74.0 2.2 mg/g EO). This oil was tested against microorganisms that affect cocoa production in Colombia and in tropical countries where the production of this commodity is very important for the economy. The antifungal tests were performed on the fungal species Moniliophthora roreri and showed promising and significant activity, inhibiting growth by more than 95% at concentrations of 50 L/mL and 100 L/mL. This remarkable antifungal activity could be due to the presence of major and minor compounds that synergistically enhance the activity.